2009
DOI: 10.1080/03009740802279709
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spironolactone on endothelial dysfunction in rheumatoid arthritis

Abstract: The study suggests that, in RA, endothelial dysfunction is part of the disease process and treatment with spironolactone improves both endothelial dysfunction and inflammatory disease activity in RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 32 publications
4
19
0
Order By: Relevance
“…To confirm that the abnormal response of vessels from AIA rats to ACh was not due to decreased response of vascular smooth muscle cells to NO, we demonstrated that the relaxing effect of the NO donor SNP was not impaired in the AIA rats. This result is in accordance with recent study findings in AIA rats (12,14,36) as well as in RA patients (37)(38)(39)(40). Likewise, we verified that the contractile response of vessels from AIA rats to NE was not different from that of control rats.…”
Section: Discussionsupporting
confidence: 93%
“…To confirm that the abnormal response of vessels from AIA rats to ACh was not due to decreased response of vascular smooth muscle cells to NO, we demonstrated that the relaxing effect of the NO donor SNP was not impaired in the AIA rats. This result is in accordance with recent study findings in AIA rats (12,14,36) as well as in RA patients (37)(38)(39)(40). Likewise, we verified that the contractile response of vessels from AIA rats to NE was not different from that of control rats.…”
Section: Discussionsupporting
confidence: 93%
“…62 Treatment with spironolactone has been shown to improve the endothelial dysfunction and inflammatory disease activity in rheumatoid arthritis. 63 Although the beneficial effects of spironolactone in attenuating neuropathic pain have been described as being due to its aldosterone receptor blockade activity, some studies have suggested that the suppressive effect of spironolactone on immune-reactive and inflammatory cytokines is independent of mineralocorticoid receptor blockade. Furthermore, the direct role of pro-renin receptors in decreasing inflammatory cytokines and producing beneficial effects in neuropathic pain may not be completely ruled out in aliskerin-mediated beneficial effects.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…In clinical trials, markers of chronic low-grade inflammation and endothelial dysfunction were shown to be reduced by spironolactone in rheumatoid arthritis 15 and by eplerenone in essential hypertension. 16 From previous long-term prospective studies we have seen that in type 1 2 and type 2 diabetes, 4 lower levels of markers of endothelial dysfunction and inflammation are associated with a better outcome regarding cardiovascular morbidity, renal disease and all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%